The Impact of High Labour Turnover on Students Performance in Private Higher Institutions of Learning in Kabale District: A Case Study of African College of Commerce and Technology (ACCT) And African International Christian Ministry (AICM). - Kemigisha, Maryshivan (Kabale University, 2024)
This research aimed to assess the impact of high labor turnover on the performance of students in private higher institutions of learning, focusing on ACCT and AICM as case studies. The study was guided by three specific objectives: identifying the causes of high labor turnover and its effect on performance, determining the effects of high labor turnover on student performance, and proposing solutions to high labor turnover at AICM and ACCT. The study employed a cross-sectional research design with both qualitative and quantitative approaches. Data was collected from 73 respondents, including top administrators, lecturers, and students, using questionnaires and interview guides. The collected data was checked for errors, coded, and entered into an Excel computer package for analysis, and then presented in tables as frequencies and percentages. Empirical findings revealed that the major cause of high turnover at AICM and ACCT was the lack of staff engagement and motivation, as reported by 27.4% of respondents. The major effect of high labor turnover on student performance was a reduced availability of mentors and advisors, also noted by 27.4% of respondents. The best solution to high labor turnover, according to 27.4% of respondents, was recognizing and rewarding employee contributions. The study recommended that the heads of these institutions should conduct regular salary and benefits benchmarking to ensure competitive compensation packages within the teaching industry. Adequate healthcare, retirement plans, and other non-monetary benefits should also be considered to enhance employee satisfaction and retention. Additionally, stakeholders should establish structured career growth opportunities for employees, including mentorship programs, training sessions, and workshops aimed at developing specific skills that align with both personal and institutional goals. Clear paths for advancement within the organization can motivate employees to stay and contribute to their professional growth.